Increased risk for dementia in neurofibromatosis type 1 - Kallionpää Roope A; Valtanen Mikko; Auranen Kari; Uusitalo Elina; Rinne Juha O; Peltonen Sirkku; Peltonen Juha (Nature Publishing Group, 2022)
Purpose: To determine the risk for dementia in neurofibromatosis type 1 (NF1) using a Finnish nationwide cohort of individuals with NF1, and data from national registries.
Methods: A Finnish cohort of 1,349 individuals with confirmed NF1 according to the US National Institutes of Health (NIH) diagnostic criteria was compared with a control cohort of 13,870 individuals matched for age, sex, and area of residence. Dementia-related hospital visits were retrieved from the Finnish Care Register for Health Care using International Classification of Diseases, 10th revision (ICD-10) diagnosis codes G30 and F00-F03. Purchases of antidementia drugs were queried with Anatomical Therapeutic Chemical (ATC) classification code N06D from the drug reimbursement register maintained by the Social Insurance Institution of Finland. The follow-up spanned 1998-2014.
Results: Totals of 16 and 165 individuals with at least two dementia-related diagnoses or drug purchases were identified in the NF1 and control cohorts, respectively. The hazard ratio for dementia in NF1 was 1.67 (95% confidence interval [CI] 1.00-2.80, P = 0.050). In an analysis stratified by the type of dementia, the risk for Alzheimer disease was increased in NF1 compared to controls with a hazard ratio of 2.88 (95% CI 1.47-5.66, P = 0.002).
Conclusion: Dementia and especially Alzheimer disease are previously unrecognized neurological complications of NF1.
© 2021. The Author(s).